Exploring Muslim Tourist Needs at Halal Spa Facilities to Support Indonesia's Sharia Tourism - Faidah, Mutimmatul (The international journal of religious tourism and pilgrimage, 2021)
This study reviews Islamic laws related to body spa services and describes the spa facilities which Muslim tourists need. This descriptive qualitative study involved spa consumers, owners, therapists, and religious leaders. The data were collected using interviews, focus group discussions, and observation. This study was analysed via Maqasid al-Shariah (the objectives of Islamic law) and the Classification of Benefits based on Shariah theory. The results show that the process and purpose of spas should be for the sake of maslahah (public interest). Based on Maqasid al-Shariah(the objectives of Islamic law), spa services benefit the Hifd al-'Aql (preservation of intellect) and Hifd al-Nafs (preservation of life). There were three levels of Complementary Needs for spas, categorised as Daruriyyat (Basic Necessities), Hajiyyat (Complementary Needs), and Tahsiniyyat (Embellishment), while the spa facilities comprise 14 elements.